Effect of temperature on synthesis of cellulose nanoparticles via ionic liquid hydrolysis process - Samsudin N.A.; Low F.W.; Yusoff Y.; Shakeri M.; Tan X.Y.; Lai C.W.; Asim N.; Oon C.S.; Newaz K.S.; Tiong S.K.; Amin N. (Elsevier B.V., 2023)
Catalysts; Cellulose; Crystallinity; Field emission microscopes; Fourier transform infrared spectroscopy; Hydrolysis; Ionic liquids; Microcrystals; Nanoparticles; Scanning electron microscopy; Synthesis (chemical); X ray diffraction; Cellulose nanoparticles; Effect of temperature; Field emission scanning electron microscopy; Green chemistry approaches; Hazardous waste products; Micro-crystalline cellulose; Preferential orientation; Structural transformation; Thermogravimetric analysis; Catalysts; Cellulose; Crystallinity; Gravimetry; Hydrolysis; Scanning Electron Microscopy; Thermal Analysis; X Ray Diffraction